Effects of Thickness and Grafting Density on the Activity of Polymer‐Brush‐Immobilized Tris(triazolyl) Copper(I) Catalysts. Issue 5 (23rd January 2015) - Fernandes, Antony E.; Ye, Qian; Collard, Laurent; Le Duff, Cécile; d'Haese, Cécile; Deumer, Gladys; Haufroid, Vincent; Nysten, Bernard; Riant, Olivier; Jonas, Alain M.
Abstract We report herein the application of polymer brushes for the immobilization of tris[(1, 2, 3‐triazolyl)methyl]amine CuCl catalysts. Well‐defined catalytic brushes were prepared through grafting‐from and postpolymerization modification approaches on Si surfaces and characterized by X‐ray reflectivity, X‐ray photoelectron spectroscopy, and inductively coupled plasma mass spectrometry. Hairy catalysts of varying thickness and grafting density were investigated in a model CuI‐catalyzed azide–alkyne cycloaddition reaction and showed remarkable activity at loadings as low as 0.02 mol % as a result of the unique catalytic site density and nuclearity found in the brush. We demonstrate that thickness and grafting density parameters can be adjusted to maximize catalytic activity along the brush thickness.